Corporate disclosure, transparency and cost of equity capital: evidence from Ghana's stock market. (1st January 2013) - Bokpin, Godfred A.
This paper finds, consistent with Lopes and de Alencar (2010), that the strength of association between corporate information disclosure and cost of capital depends on the corporate disclosure environment. This paper finds that in an environment where disclosure requirement is not rich, the higher variation from the disclosure practices of firms leads to significant lower cost of equity capital. Corporate firms that commit resources to increased information disclosure and transparency are compensated with lower cost of equity capital, reduced information asymmetry between corporate insiders and investors which leads to lower or little discount on their shares hence the lower cost of equity capital reported. Corporate disclosure and transparency is statistically significantly negatively related to cost of equity capital on the Ghana Stock Exchange (GSE).